Sliding mode control of grid connected brushless doubly fed induction generator driven by wind turbine in variable speed - MA. Mahboub; S. Drid; MA. Sid; R. Cheikh (International Journal of System Assurance Engineering and Management, 2017)
This paper proposes a robust sliding mode control of grid-connected brushless doubly fed induction generator (BDFIG). The developed algorithm is based on the decoupling control by using oriented grid flux vector control strategy. The decoupling of the active and the reactive stator powers insures an optimal performance of the BDFIG at the sub-synchronous region. The stability analysis of the closed-loop system is rigorously proved using a Lyapunov approach. The robustness of the proposed control with respect to parameter variation is illustrated by simulation results. Furthermore, a maximum power point tracking strategy is added to enhance the wind energy conversion system efficiency.